Extraction of Meaningful Information from the Web: a Brief Survey - V. Chobe, Santosh; Shirish S. Sane, Dr. (International Journal of Engineering and Technology, 2018)
There is an explosive growth of information on Internet that makes extraction of relevant data from various sources, a difficult task for its users. Therefore, to transform the Web pages into databases, Information Extraction (IE) systems are needed. Relevant information in Web documents can be extracted using information extraction and presented in a structured format.By applying information extraction techniques, information can be extracted from structured, semi-structured, and unstructured data. This paper presents some of the major information extraction tools. Here, advantages and limitations of the tools are discussed from a userâ€™s perspective.Â Â